2017
DOI: 10.1093/dote/dow011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of peroral endoscopic myotomy for patients with achalasia: a retrospective single-center study

Abstract: Peroral endoscopic myotomy (POEM) has been widely applied to the treatment of achalasia. The aim of this study is to retrospectively investigate the long-term outcome of POEM in patients with achalasia. Patients undergoing POEM at our center with a minimum follow-up of 3 years were enrolled in this study. Relief of patients' symptom was defined as the primary outcome. Secondary outcomes included lower esophageal sphincter pressure, esophageal emptying, symptoms relapse, and clinical reflux adverse events. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Patients with achalasia who undergo POEM have high rates of esophageal acid exposure putting them at risk for development of BE and esophageal adenocarcinoma 6 7 . Routine post-procedure pH testing and EGD evaluation have demonstrated rates of abnormal acid exposure and esophagitis in the range 28 – 58 % and 17 – 31 %, respectively in published series 1 2 3 4 5 . Endoscopic fundoplication (TIF) is an exciting new treatment option for patients with GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with achalasia who undergo POEM have high rates of esophageal acid exposure putting them at risk for development of BE and esophageal adenocarcinoma 6 7 . Routine post-procedure pH testing and EGD evaluation have demonstrated rates of abnormal acid exposure and esophagitis in the range 28 – 58 % and 17 – 31 %, respectively in published series 1 2 3 4 5 . Endoscopic fundoplication (TIF) is an exciting new treatment option for patients with GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Peroral endoscopic myotomy (POEM) has emerged as a safe and efficacious therapeutic option for patients with achalasia with efficacy rates upwards of 90 % 1 . However, with successful decrease in lower esophageal sphincter (LES) pressure to relieve symptoms of dysphagia comes the reciprocal consequence of increased acid exposure into the esophagus often requiring long-term proton-pump inhibitor (PPI) use 1 2 3 4 5 . Given the known association between long-standing gastroesophageal reflux (GERD) and the development of Barrett’s esophagus (BE) 6 and esophageal adenocarcinoma 7 , as well as the increasing adverse health effects of long-term PPI use 8 9 , such high incidences of post-procedural esophageal acid exposure have significant potential consequences.…”
Section: Introductionmentioning
confidence: 99%
“…52 With regard to POEM treatment, 3 of the 7 studies reported that achalasia type III was associated with failure. [53][54][55] Two Botox studies described that vigorous achalasia was found to be a predictor of good response. 25,56 Other manometric factors.…”
Section: Diagnostic Predictorsmentioning
confidence: 99%
“…The efficacy of POEM in studies reporting long-term outcomes is between 80%-90%, suggesting that the response is durable after POEM. [62][63][64][65] The longterm efficacy of POEM remains to be seen in large, prospective studies as these studies are mostly retrospective with only a proportion of patients completing entire follow-up.…”
Section: Technique Of Poem and Variationsmentioning
confidence: 99%